Interpersonal Communication Patterns Between Teachers and Students in MTS Tahfidzul Qur'an Development in Nurul Azmi at Kelurahan Tangkahan, Medan Labuhan - Dwi Karmila; Muhammad Alfikri (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
Communication is a direct or indirect contact relationship between humans, be it individuals or groups. Interpersonal communication in the foundation between educators and students is an important element for knowing moral development. Every educator, has a special method for teaching and caring for students. The aim of this study was to describe the pattern of interpersonal communication between educators and students in moral development and to describe the relationship between educators and students after using the pattern interpersonal communication at MTS Tahfidzul Qur’an Nurul Azmi in Martubung. This study applies a descriptive qualitative approach. Sources of data obtained by in-depth interviews, observation and documentation through educators and students. The results of research conducted at MTS Tahfidzul Qur’an Nurul Azmi Martubung showed that interpersonal communication between educators and students during the moral development process went very well.